AN ANALYSIS OF ERRORS MADE BY UZBEK LEARNERS OF ENGLISH IN USING PREPOSITIONS (Ustozlar uchun, 2026)
This research studies the common errors made by Uzbek learners while using English prepositions. The article mainly focuses on the reasons behind these mistakes and the effect of the Uzbek language on English learning. Different examples from students’ written tasks and speaking activities are analyzed in the research. Error analysis and descriptive analysis methods are used in order to identify the most common problems. The research also explains how grammar differences between Uzbek and English create difficulties for learners. The results show that many learners confuse prepositions such as “in,” “on,” and “at,” or omit them completely in sentences. The article may help English teachers understand learner problems better and choose more useful teaching activities for grammar lessons. More attention to practice and contextual learning can improve students’ accuracy in using prepositions.